PENGARUH WAKTU PENYIMPANAN TERHADAP JUMLAH ERITROSIT DARAH DONOR - Tadjuddin Naid; Dzikra Arwie; Fitriani Mangerangi (As-Syifaa Jurnal Farmasi, 2012)
A research about the effect of blood storage time to the number of erythrocyte cell count in blood donors has been done at Transfusion Blood laboratory Unit and of laboratoriun Health Of Job Society. This research is aimed to determine the effect of blood storage time to the number of erythrocyte cell count in blood donors which placed at 4o C. This study used experiment laboratory method, with total samples are 5 bags of blood. The result of the research about eritrocyte cell count decresed every week, 4,72% (man) and 5,45% (woman) at the first week, 8,83% (man) and 10,9% (woman) at the second week, 14,17% (man) and 15,53% (woman) at the third week, 21,77% (man) and 25,34% (woman) at the fourth week and 30,39% (man) and 32,7% (woman) at the fifth week.Keywords : storage time, caffeine, erythrocyte, blood donor